Hydroxychloroquine as an adjunct therapy for diabetes in pregnancy - Basri, Nurul Iftida; Murthi, Padma; Abd Rahman, Rahana (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This review discusses the pathophysiology of diabetes in pregnancy in relation to the placental function. We review the potential use of hydroxychloroquine in improving pregnancy outcomes affected by diabetes. The review focuses on the mechanism of action of hydroxychloroquine and its potential effects on diabetes. There are several pathways in which hydroxychloroquine mediates its effects: through the inflammasome complex, inflammatory cytokines, oxidative stress, modulatory effects, and antihyperglycemic effects. As a safe drug to be used in pregnancy, it is worth exploring the possible use hydroxychloroquine as an adjunct treatment to the current therapy of diabetes in pregnancy.